Communication enclosing ordinance of secession and resolution of the state of Louisiana : also joint resolutions from the states of Indiana and New York : February 12, 1861 (Document (Virginia. General Assembly. Senate), 1861)
February 1861 communication transmitting the ordinance of Secession from Louisiana, and joint resolutions from New York and Indiana appointing and sending commissioners to the February 4th Washington convention. These communications were sent to Governor John Letcher and subsequently transmitted to the Virginia General Assembly.